One-Dimensional Heat Conduction Through Composite Walls. - Higley, Savanah L.; Siahpush, Ali S. (Journal of the Utah Academy of Sciences, Arts & Letters, 2024)
One-dimensional (1D) heat transfer analysis is a fundamental assumption to make when the thermal behavior of a system is considered. This assumption states that if the thickness of a material is considerably less than the height and length, heat conduction can be assumed to be 1D. This assumption can be used to simplify the conduction heat transfer analyses, including that of a composite wall. In this experiment, a composite wall was considered with oak wood, polylactic acid, and acrylic materials in both parallel and series, and the temperatures at various points were measured to verify the validity of 1D heat transfer. The experimental temperature values were compared with transient analytical values obtained through an explicit finite difference method code executed in MATLAB, and steady-state analytical values were obtained by applying the thermal resistance concept. This experiment proved to be a success in validating 1D heat transfer, as the experimental temperature values were similar to both the transient and steady-state analytical values. Minimal error was observed in the experiment. Further uses of this experiment include a heat transfer laboratory demonstrating the 1D heat transfer concept.